If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) = 2x + -1(-3) + x Reorder the terms: 3(1 + x) = 2x + -1(-3) + x (1 * 3 + x * 3) = 2x + -1(-3) + x (3 + 3x) = 2x + -1(-3) + x Multiply -1 * -3 3 + 3x = 2x + 3 + x Reorder the terms: 3 + 3x = 3 + 2x + x Combine like terms: 2x + x = 3x 3 + 3x = 3 + 3x Add '-3' to each side of the equation. 3 + -3 + 3x = 3 + -3 + 3x Combine like terms: 3 + -3 = 0 0 + 3x = 3 + -3 + 3x 3x = 3 + -3 + 3x Combine like terms: 3 + -3 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 250h=50 | | y/x=10 | | 6x+3x+y=180 | | 3f^2-7f+4=0 | | 3x-6y+ax-2y= | | 40=x+22 | | 49=7c+49 | | -8b+5b=-16-b | | 20xy=56 | | 2(x)-3=x-5 | | y=4*0.2x | | N^2-2=8N | | -116=8(3-3v)+4v | | 7x-10+3x+6=106 | | %=40/1000 | | N^22=8n | | 153=-8(-3+2a)+1 | | 57=9+4u | | 228=-4(-1+7a) | | -3x(2)=2x(3) | | 5s^2-50s+45=0 | | 5.7s+8.1=-5.5 | | 9x^2+288=0 | | 5/x=10/25 | | 198=4(1-7p)-2 | | 25x=50x | | 2x+24=7x | | ((2)10/17)*3/10 | | 60x^3+54x^2-6m=0 | | 18j^2+5j=0 | | 9y+3x=45 | | 6×4/12= |